Pengaruh Inovasi Teknologi, Literasi Keuangan, Dan Lingkungan Sosial Terhadap Minat Berinvestasi Di Pasar Modal Secara Komparatif - Dini, Dini Putri Pebriani; Arisandy, Yosy; Polindi, Miko (JPSDa: Jurnal Perbankan Syariah Darussalam, 2025)
This study aims to compare the influence of technological innovation, financial literacy, and social environment on students’ interest in investing in the sharia capital market at three universities: UIN Fatmawati Sukarno Bengkulu, Universitas Muhammadiyah Bengkulu, and Universitas Bengkulu. The background of this research is the rising trend of interest among Generation Z, particularly university students, in technology-based investments, financial awareness, and the influence of their social environment. This research used a quantitative approach with a survey method by distributing questionnaires to 112 respondents. The data were analyzed using multiple linear regression with the help of SPSS version 25. The findings indicate that, individually, technological innovation, financial literacy, and social environment positively and significantly affect interest in investing in the Islamic capital market. Collectively, these three variables also have a significant impact. These findings highlight the importance of enhancing financial literacy, optimizing the use of technology, and strengthening the role of the social environment in fostering investment interest among students, as well as creating a supportive social climate to encourage student participation in investment activities.